Android-Based Geographic Information System (GIS) in Making Village Location Maps in Bengkulu City - Agil Setiawan; Herlina Latipa Sari; Arius Satoni K (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Geographic Information System is one of the information management systems whose development is very fast along with the increasing development of human intelligence. In its development, what is needed to develop a Geographic Information System is data and information. Geographic Information System is very important for the development of an area. One of them is the Geographic Information System about the location of urban villages in Bengkulu City. The presence of the Geographic Information System is expected to provide convenience to people who need information about the location of urban villages in Bengkulu City. In this study, an application was developed by implementing a Geographic Information System that was able to display a map of the location of the village head office with the help of Google Map Api, and also the basis of this application there were two types, namely Web and Android. This Geographic Information System is divided into 2 application parts, namely web-based applications and Android-based applications. For data processing using a web application, while to get information about the location of the village head office can use the android application. Based on the results of the tests that have been carried out, with black box testing, it was found that the Android application succeeded in automatically displaying the location of the village head office along with information and routes.